A MEDIA YOUTUBE EFEKTIV TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA DI SMA NEGERI KOTA BENGKULU: MEDIA YOUTUBE EFEKTIV TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA DI SMA NEGERI KOTA BENGKULU - Ariyanto, Rahmat (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2023)
Reports on children's health activities at the high school level show that 70 young girls are at risk of anemia. Adolescent girls are very susceptible to anemia due to reduced supply of iron for erythropoesis, due to bare metal reserves which ultimately result in reduced hemoglobin formation. One way to increase the knowledge and attitudes of young women about anemia by providing health promotion using Youtube. The purpose of this study was to determine the effectiveness of health promotion throughmedia YouTube on the knowledge and attitudes of adolescent girls about anemia in Bengkulu City High School in 2020. This type of research is a quasy experimental study with a pretest posttest Group Control design design in which sample members in the intervention and control groups are conducted by purposive sampling, with a total sample of 56 respondents with each group of 28 respondents. The results showed a significant difference in the knowledge and attitudes of anemia in young women before and after health promotion both in the intervention group (p = 0,000) and in the control group (p = 0,000). There was a significant difference in the level of knowledge and attitude of anemia among young women in the intervention and control groups (p = 0,000). Health promotion throughmedia YouTube gives higher results compared to leaflet media with the difference in knowledge (24.46) and attitude (26.50). Means showingmedia is youtube more effective than the media leaflets on the knowledge and attitudes of young women about anemia in Bengkulu City High School. It is expected that themedia YouTube can be used as a reference in providing health promotion about anemia in young women to improve knowledge and attitudes.